Sustainable Agritourism as a Development Lever in Algeria’s Arid Regions: A Quantitative Approach to Identifying the Most Suitable Sites (The Case of Biskra, El Oued, and Ghardaïa) - Mokhnane, Tarek; Khiari, Reguia; Adjlane, Sabah (Journal Algérien des Régions Arides, 2026)
Sustainable agritourism represents a promising pathway for rural devel-opment in arid regions. This study aims to identify the most suitable loca-tions for sustainable agritourism development in Algeria’s drylands using an integrated quantitative approach combining Data Envelopment Analysis (DEA), the Best–Worst Method (BWM), and the Spherical Fuzzy Combined Compromise Solution (SF-CoCoSo). The empirical application focuses on three southern Algerian provinces — Biskra, El Oued, and Ghardaïa — which exhibit distinct agricultural and environmental profiles. Findings reveal that Biskra ranks highest due to its diversified agricultural production and robust infrastructure, followed by El Oued for its innovative farming systems, and Ghardaïa for its heritage and cultural tourism potential despite limited water resources. The study concludes that integrating quantitative decision-making models provides a more objective foundation for agritourism site selection and contributes to sustainable development planning in Algeria’s arid zones
Keywords: Agriculture -- Mzab

الشهيد الحاج عمر بن حمو علوط في التنمية: العمرانية والفلاحة - دادي او عيىس, كير بن محمد (الشهيد الحاج عمر بن حمو علوط: أنموذج التضحية في العمل الاجتماعي (1947-2016), 2025)
Keywords: Agriculture -- Mzab; Biographies -- Mzab -- 20e siècle; Conflits -- Mzab

Mindennek a kulcsa a víz – hagyományos öntözőrendszerek arid körülmények között - Somogyi, Norbert; Czóbel, Szilárd; Szarvas, Adrienn; Jani, Péter; Gera, Magdolna; Duray, Balázs (Agrofórum : a növényvédők és növénytermesztők havilapja, 2025)
Keywords: Agriculture -- Mzab

Inventaire, Evaluation et étude de la répartition du Pistacia atlantica Desf dans les communes de Beriane et Guerrara (wilaya de Ghardaia). - Lassakeur, Mouna; Ben Alia, Zohra (Université de Ghardaia, 2025)
Keywords: Agriculture -- Mzab

Traditional Irrigation installations in the M’zab Valley - Zaaba, Omar (Herodotus' Journal of the Human and Social Sciences, 2025)
Keywords: Agriculture -- Mzab; Irrigation -- Mzab; Puits -- Mzab

Agriculture des régions arides et hyper-arides : Entre les potentialités, les contraintes et la capitalisation des expériences - Benchentouf, M. (El Watan, 2024)
Keywords: Agriculture -- Mzab

اثر استراتيجية الفلاحة الصحراوية في الجزائر على الاقتصاد الوطني: ولاية غرداية نموذجا = The Impact of Desert Farming Strategy in Algeria on the National Economy: The Case of Ghardaia Province - سويد, هاجر; أولاد العيد, بوحفص (مجلة الإقتصاد والتجارة الدولية, 2024)
Keywords: Agriculture -- Mzab

Désert, jardins, gestion de l'eau : revivifier la terre - Moussaoui, Abderrahmane; Biase, Alessia de (Suspended spaces, 2024)
Keywords: Agriculture -- Mzab

Effect of the structural composition of a Saharan agricultural landscape on bird communities in the Algerian Northen Sahara - Bekrara, Oussama; Guergueb, El-Yamine; Haddad, Soumia; Nouidjem, Yassine; Bounab, Choayb; Khammar, Hichem (Forestry Ideas, 2024)
Keywords: Agriculture -- Mzab; Faune -- Mzab

Quantitative Analysis and Efficiency Assessment of Floodwater Harvesting System in Arid Region: Case of Touzouz ephemeral stream—Mzab Valley - Bahmed, Ali Taleb; Bouzid-Lagha, Souad (Water Resources, 2020)
Keywords: Agriculture -- Mzab